2008
DOI: 10.1124/mol.108.045682
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Inhibition of Serine Protease Processing Requires a High Fractional Inhibition of Cathepsin C

Abstract: Inhibition of cathepsin C, a dipeptidyl peptidase that activates many serine proteases, represents an attractive therapeutic strategy for inflammatory diseases with a high neutrophil burden. We recently showed the feasibility of blocking the activation of neutrophil elastase, cathepsin G, and proteinase-3 with a single cathepsin C selective inhibitor in cultured cells. Here we measured the fractional inhibition of cathepsin C that is required for blockade of downstream serine protease processing, in cell-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 35 publications
2
54
1
Order By: Relevance
“…For this therapeutic application, CatC activity must be reduced by Ͼ95%. Our data support the conclusions of Méthot et al (25,26) who reported that very high fractional inhibition of the CatC activity by chronic administration of a CatC inhibitor is required to prevent the activation of NSPs in vivo. CatH has been shown to serve as a backup for CatC-mediated granzyme B activation in cytotoxic lymphocytes (38).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…For this therapeutic application, CatC activity must be reduced by Ͼ95%. Our data support the conclusions of Méthot et al (25,26) who reported that very high fractional inhibition of the CatC activity by chronic administration of a CatC inhibitor is required to prevent the activation of NSPs in vivo. CatH has been shown to serve as a backup for CatC-mediated granzyme B activation in cytotoxic lymphocytes (38).…”
Section: Discussionsupporting
confidence: 82%
“…In the past years dipeptidyl nitriles have attracted great attention due to their strong inhibitory activity against human CatC (23,24). Inactivation of CatC in the bone marrow of rats by treating them with a reversible cyclopropyl nitrile inhibitor for 2 weeks at doses that resulted in the nearly complete inhibition of CatC only partially prevents activation of NSPs (25). Thus, a continuous very high degree of CatC inhibition is required to effectively block the maturation of downstream elastase-like NSPs in vivo (25,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that cathepsin C may be an attractive drug target to control multiple inflammatory serine proteases. Nonetheless, it appears that efficient and sustained inhibition of the enzyme will be required to fully quench neutrophil granule protease activity [63]. Cathepsin C may itself be regulated by cystatin F. Cystatins are a family of proteinaceous cysteine protease inhibitors, some of which bind very tightly to cathepsin active sites [64].…”
Section: Activation Of Granule Serine Proteasesmentioning
confidence: 99%
“…3 There is increasing evidence that cathepsin C plays a key role in a variety of diseases, including sepsis, 4 arthritis, 5 and other inflammatory disorders. [6][7][8][9][10][11][12] From knockout mice studies, it appears that cathepsin C is coexpressed and acts as a physiological activator of the neutrophil-derived serine proteases: neutrophil elastase, cathepsin G and proteinase 3,5 the mast cell chymase and trypase, 13 and the lymphocytes derived granzymes A and B.…”
mentioning
confidence: 99%